Maroccaro rock glacier, Val di Genova, Italian Alps. - Seppi R.; Baroni C.; Dall’Amico M.; Rigon R.; Zampedri G.; Zumiani M.; CARTON, ALBERTO (country:CHE, 2011)
In 2001 we started a topographic study on an active rock glacier (named Maroccaro rock glacier, acronym MaRG, coordinates: 46° 13’ 06” N, 10° 34’ 34” E) located in the AdamelloPresanella massif (Central Italian Alps). Since 2004, also the nearsurface ground temperature was measured using a miniature data logger. Our data show that in eight years (20012009) MaRG has moved downslope with average velocities ranging from 0.02 to 0.21 m/year. The velocity reaches a maximum in the middle and the lower part of the rock glacier, and decreases towards the upper sector, where the surveyed boulders are almost stationary. A considerable different velocity from year to year has been observed, but no clear trends seem to emerge from the mean annual displacement rate. On the rock glacier the evolution of the ground temperature since 2004 is directly associated with the air temperature and the snow conditions, in terms of thickness and duration of the snowpack. The ground has warmed significantly both in 2007, after a very mild and little snowy winter, and in 2009, after a cold but exceptionally snowy winter. The displacement rate of MaRG seems to rapidly react to the ground temperature variations, apparently without any time delay. The exceptionally snowy winter 2008/09 seems to have played a significant role on the displacement rate, causing ground temperature increase and, probably, an increase in velocity, which reached its maximum in the year.